Comprehensive test in school physical education at secondary schools in the Czech Republic - Standardization and verification [Vědomostní test ve školní tělesné výchově na středních školách v ČR - Standardizace a verifikace] - Karel Frömel; Filip Neuls; Jana Vašíčková (Palacky University, 2010)
BACKGROUND: Physical education is at present oriented to the practical realization of physical activities (PA); less time is devoted to the acquisition of certain knowledge about the importance of PA and other necessary information about a healthy lifestyle and nutrition. OBJECTIVE: The main aim of the study is to penetrate the knowledge sphere of students in the field of a physically active lifestyle and health and thus to standardize the comprehensive test in a Czech environment. Further, to compare test results among the types of schools, classes and gender. METHODS: For testing knowledge about health and PA, we designed a comprehensive test that was distributed at 10 secondary schools in the Czech Republic (two vocational schools and eight grammar schools). We obtained tests from 192 boys and 224 girls (15 to 19 year olds) who completed the test twice: as a pre-test and after five weeks as a post-test in 2008-2009. In total, we gathered 832 tests. RESULTS: The reliability coefficient (half split method) was rtt = 0.527 (p < 0.01). Cronbach's alpha of inner consistency was r = 0.627. Neither boys nor girls reached 50% of the correct answers in the test. No difference has been found between gender in the pre-test; in the post-test a significant difference was found, which was confirmed also by the effect size (d = 0.35). Grammar school students (d = 0.87) and students from higher classes (d = 0.47) had better knowledge about health and PA when compared to vocational school students and first year students. CONCLUSIONS: The comprehensive test can be used mainly for research, comparison and as a part of a complex scientific survey. Grammar school students and older students scored better on the test, we did not find any gender differences. Students reached the lowest score in the nutritional and educational sphere. Practical use of the comprehensive test can encourage pupils and students to think about their own healthy lifestyle. In order to change pupils' physical behavior we may involve pupils more and use, for instance, pedometers for step monitoring. [VÝCHODISKA: Tělesná výchova je v současné době orientována na praktickou realizaci pohybových aktivit (PA), méně času se věnuje předávání příslušných vědomostí o významu realizace PA a dalších nezbytných informací o zdravém životním stylu a výživě. CÍLE: Hlavním cílem studie je proniknout do vědomostní sféry studentů, která zasahuje zejména oblast biologie člověka, výživy a znalostí z oblasti tělesné výchovy a sportu, a tak standardizovat vědomostní test o problematice zdraví a pohybové aktivity v českých podmínkách. Dílčím cílem je pak porovnat výsledky vědomostního testu z hlediska typu škol, tříd a pohlaví. METODIKA: Pro zjišťování vědomostí o problematice zdraví a PA byl sestaven vědomostní test, který byl předložen žákům na 10 středních školách v České republice (dvě odborné školy a osm gymnázií). Získali jsme vyplněné testy od 192 studentů a 224 studentek (15–19 let), kteří je vyplňovali dvakrát: jako pre-test a po pětitýdenní pauze jako post-test v letech 2008–2009. Celkem bylo shromážděno 832 testů. VÝSLEDKY: Koeficient reliability metodou půlení testů byl zjištěn rtt = 0,527 (p < 0,01). Cronbachovo alpha vnitřní konzistence bylo r = 0,627. Chlapci ani děvčata nedosahují 50 % správných odpovědí na otázky vědomostního testu. V pre-testu nebyl zjištěn žádný rozdíl mezi pohlavími; v post-testu byl zjištěn významný rozdíl, který byl také potvrzen koeficientem "effect size" (d = 0,35). Gymnaziální studenti (d = 0,87) a studenti vyšších ročníků (d = 0,47) mají větší znalosti o problematice zdraví a PA než studenti středních odborných škol a prvních ročníků. ZÁVĚRY: Vědomostní test je využitelný zejména pro výzkumné účely, komparaci a jako součást rozsáhlejšího výzkumného šetření. Studenti gymnázií a starší studenti dosahovali lepších výsledků v testu než studenti středních škol a nižších ročníků; mezi pohlavím nebyly zjištěny žádné rozdíly. Praktické použití vědomostního testu by mohlo vést žáky a studenty k zamyšlení se nad vlastním životním stylem. Pro změny pohybového chování by pak bylo vhodné více zainteresovat žáky a využít např. monitorování PA krokoměrem.]